Igualdad ante la ley: la nación socio étnica de Francisco Laso - Abadía González, Eugenia María (2020)
This article is an analysis of Francisco Laso's painting Igualdad ante la Ley or Las tres razas. Through an intimate and opposite scene to reality, Laso shows us an ideal of society and his desires to achieve equality between different socio-ethnic groups. The important one of the painting is that it highlights the socio-ethnic differences of Peru in the mid-nineteenth century. Likewise, the political and economic nature of the context in which the painting was carried out when dealing with the issue of slavery, child labor and indigenous tribute. In addition, as a cultural historical document shows us the dress of the time that determines the role of people in the Lima society of the XIX century.